Morphological, physiological and biochemical properties of heavy metal resistant isolates of bacteria obtained from different Antarctic substrates - Hnatush, S.; Peretyatko, T.; Maslovska, O.; Moroz, O.; Komplikevych, S.; Kondratiuk, T. (Ukrainian Antarctic Journal, 2020)
Aim. To investigate the cultural, morphological, physiological and biochemical properties of the isolated chemoorganotrophic heavy metal resistant isolates of bacteria from different samples obtained during the Ukrainian Antarctic expedition in 2019 for further selection of the most resistant to heavy metal compounds and biochemically active substances. Methods. Pure cultures of bacteria were isolated using tryptone soy agar and nutrient agar. Obtained isolates were sown on agar media containing Cu(II) (0.3, 0.1, 1.5, 8, 78 mM), Pb(II) (0.00009, 0.0005, 0.005, 0.05, 0.5 mM), Cr(VI) (0.00096, 0.0096, 0.96, 9.6 mM). The morphological properties of the bacteria were studied using an Axio Lab.A1 Carl Zeiss binocular microscope, an Olympus IX73 inverted microscope with DP-74 digital camera and transmission electron microscopy. Endospores were detected using the Peshkov-Trujillo method. Catalase, oxidase, amylase, lipolytic, protease activities, ability to fix nitrogen were determined. The ability of microorganisms to metabolize organic carbon sources was determined during growth on Hiss medium with different carbohydrates and alcohols. The determination of the physiological properties of obtained isolates was performed using the Remel RapID™ ANA II system. Results. 92 isolates of psychrophilic microorganisms that grew at temperatures 2 °C, 6 °C and 20 °C were isolated from investigated samples. Among the isolated microorganisms, 64 grew on media containing 0.3–1.6 mM Cu(II), or 0.00009–0.004 mM Pb(II) or 0.01–0.9 mM Cr(VI). 9 isolates of psychrophilic bacteria were resistant to Cu(II) (1.5–78 mM), Pb(II) (0.5 mM), Cr(VI) (0.96–9.6 mM). Morphological, physiological and biochemical properties of 9 multiresistant isolates were described. Conclusions. The physiological and biochemical properties of obtained isolates of An tarctic microorganisms that are resistant to Cu(II) (1.5–78 mM), Pb(II) (0.5 mM), Cr(VI) (0.96–9.6 mM) are determined. Selected isolates of microorganisms are able to use monosaccharides, disaccharides, alcohols as carbon sources; possess urease, protease, lipase, aminopeptidase activities. Selected heavy metal resistant isolates can be used for further investigation and development of technologies for bioremediation of environment.